Dysregulated levels of glycogen synthase kinase-3β (GSK-3β) and miR-135 in peripheral blood samples of cases with nephrotic syndrome - Ardalan, Mohammadreza (PeerJ, 2020)
BACKGROUND: Glycogen synthase kinase-3 (GSK-3β) is a serine/threonine kinase with multifunctions in various physiological procedures. Aberrant level of GSK-3β in kidney cells has a harmful role in podocyte injury. METHODS: In this article, the expression levels of GSK-3β and one of its upstream regulators, miR-135a-5p, were measured in peripheral blood mononuclear cells (PBMCs) of cases with the most common types of nephrotic syndrome (NS); focal segmental glomerulosclerosis (FSGS) and membranous glomerulonephritis (MGN). In so doing, fifty-two cases along with twenty-four healthy controls were included based on the strict criteria. RESULTS: Levels of GSK-3β mRNA and miR-135 were measured with quantitative real-time PCR. There were statistically significant increases in GSK-3β expression level in NS (P = 0.001), MGN (P = 0.002), and FSGS (P = 0.015) groups compared to the control group. Dysregulated levels of miR-135a-5p in PBMCs was not significant between the studied groups. Moreover, a significant decrease was observed in the expression level of miR-135a-5p in the plasma of patients with NS (P = 0.020), MGN (P = 0.040), and FSGS (P = 0.046) compared to the control group. ROC curve analysis approved a diagnostic power of GSK-3β in discriminating patients from healthy controls (AUC: 0.72, P = 0.002) with high sensitivity and specificity. CONCLUSIONS: Dysregulated levels of GSK-3β and its regulator miR-135a may participate in the pathogenesis of NS with different etiology. Therefore, more research is needed for understanding the relationship between them.